PAIKEM Model in Strengthening Creative Literacy and Poetry Writing Skills of Elementary School Students - Siti Arifa; Novi Diana; Misrina (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Creative writing, particularly poetry, is a core component of Indonesian Language instruction in elementary schools. However, fourth grade students frequently experience difficulties in composing poetry, including selecting meaningful themes, using appropriate diction, organizing poetic structure coherently, and expressing ideas creatively. Preliminary observation at Tanah Luas Public Elementary School 4 indicated that students' poetry writing achievement remained below the school's minimum mastery criterion (KKM), with a class mean score of 66.8 and only 36.0% of students achieving the required standard. This Classroom Action Research (CAR) aimed to improve students' poetry writing skills and learning activity through the implementation of the PAIKEM (Active, Innovative, Creative, Effective, and Joyful Learning) model. The study involved 25 fourth-grade students and was conducted in two action cycles, each consisting of planning, action, observation, and reflection. Data were collected through semi-structured teacher interviews, classroom observation, poetry writing tests assessed using an analytic rubric covering four dimensions (theme, diction, structure, and expression), and documentation. Data credibility was ensured through source and method triangulation. The findings demonstrate continuous improvement throughout the intervention. The class mean score increased from 66.8 in the pre-cycle stage to 75.4 in Cycle I and 84.7 in Cycle II, while the percentage of students achieving the KKM rose from 36.0% to 68.0% and 88.0%, exceeding the predetermined success criterion. The greatest improvement occurred in theme development and structural organization, whereas diction and expressive quality developed more gradually. Students also demonstrated higher levels of participation, confidence in expressing ideas, and collaborative engagement during learning activities. These findings indicate that the PAIKEM model provides an effective instructional approach for improving both poetry writing achievement and active student participation in elementary Indonesian language classrooms.